Challenges in Designing a Short Lesson Plan by Pre-Service English Teachers During an Internship School Program - Vira Oktafiyani; Hilmansyah Saefullah; Totoh Tauhidin Abbas (Institut Agama Islam Negeri Palopo, 2021)
New regulation about shortening the lesson plan in Indonesia was stated through Circular Letter no. 14 in 2019. The highlighted component of the short lesson part is lesson objective, teaching procedure, and assessment. This study was employed to explore the challenge in designing a short lesson plan by the English Pre-service Teachers. A narrative inquiry design and interview method were used to explore the challenges of designing the component of a short lesson plan. Two English pre-service teachers of the English Education Department who were experienced in the pre-service teacher training program participated in this research. The result stated that they admitted having challenges in designed teaching procedure such as selecting opening and core activities. They also having challenges in designed assessment, specifically in selecting proper indicator for evaluation on the short lesson plan.